Discrimination of hydrologic variations for spatial distribution of fish assemblage in a large subtropical temperate river - Espínola, Luis Alberto (2019)
This study examines the effects of the flow and flood pulses on spatialdispersion of fish assemblages in the floodplain of the Paraná River in Argentina. Wetested the hypothesis that high water levels and greater lateral connectivity promotefish dispersal and spatial homogenization of assemblage structure. We sampled foursites during different phases of the annual hydrologic cycle from 2010 to 2016. Watersurface in the area was estimated during each phase. We computed multivariatestatistics and estimates of ß-diversity to analyze assemblage variations in relation tohydrological phases. Three hydrological phases were defined: low flow pulses (waterlevels between 2.3 and 3.2, approximately 10% of the floodplain covered by water),high flow pulses(between 3.2 and 4.5, from 11 to 84%), and floods (> 4.5 m, morethan 84%). Although difference between high flow pulses and flood was notsignificant, ß-diversity values for these stages were higher than for low flow pulses.This suggests that floods and high flow pulses increase the spatial variability of fishassemblages, whereas homogenization processes occur later during low flowperiods. This work provides further knowledge about the flood homogenization effectin a large unregulated floodplain where lateral connectivity still plays a significant roleon ecological structuring processes.